Updates on the Clinical Evidenced Herb-Warfarin Interactions. (18th March 2014) - Ge, Beikang; Zhang, Zhen; Zuo, Zhong
Abstract : Increasing and inadvertent use of herbs makes herb-drug interactions a focus of research. Concomitant use of warfarin, a highly efficacious oral anticoagulant, and herbs causes major safety concerns due to the narrow therapeutic window of warfarin. This paper presents an update overview of clinical findings regarding herb-warfarin interaction, highlighting clinical outcomes, severity of documented interactions, and quality of clinical evidence. Among thirty-eight herbs, Cannabis, Chamomile, Cranberry, Garlic, Ginkgo, Grapefruit, Lycium, Red clover, and St. John's wort were evaluated to have major severity interaction with warfarin. Herbs were also classified on account of the likelihood of their supporting evidences for interaction. Four herbs were considered as highly probable to interact with warfarin (level I), three were estimated as probable (level II), and ten and twenty-one were possible (level III) and doubtful (level IV), respectively. The general mechanism of herb-warfarin interaction almost remains unknown, yet several pharmacokinetic and pharmacodynamic factors were estimated to influence the effectiveness of warfarin. Based on limited literature and information reported, we identified corresponding mechanisms of interactions for a small amount of "interacting herbs." In summary, herb-warfarin interaction, especially the clinical effects of herbs on warfarin therapy should be further investigated through multicenter studies with larger sample sizes.